Perspektif Gaya Kognitif: Eksplorasi Kesalahan Matematis Siswa pada Materi SPLDV - Nurmala R; Dewi Oktavia; Hariaty Hamid (FKIP Universitas Mataram, 2026)
This descriptive qualitative study maps the locations and etiological factors of mathematical errors among eighth-grade students in solving Linear Equations in Two Variables (LETV), analyzed through cognitive style typologies. Using purposive sampling, five representative subjects two Field Independent (FI) and three Field Dependent (FD) students—were selected. Data triangulation involved the Group Embedded Figures Test (GEFT), a problem-solving test, and clinical interviews, analyzed through an interactive model of reduction, display, and verification. Results indicate that FI students commit conceptual errors due to lack of thoroughness, principle errors from personalized methods, and procedural errors from unsystematic approaches. Conversely, FD students exhibit conceptual errors from misunderstanding prerequisites, principle errors in mathematical modeling, and procedural errors due to inappropriate methods and low arithmetic accuracy. The study emphasizes the necessity of instructional differentiation: teachers should provide systematization exercises for FI students to minimize carelessness and intensive scaffolding for FD students to improve their transformation of word problems into formal models. This approach aims to reduce cognitive barriers by addressing specific learning characteristics.